Utilização de usina termoelétrica a gás natural como garantidora do suprimento elétrico durante a transição energética no Paraná: estudo de caso - Rosa, Robison Armando da (2024)
Economic development brings the growing need for the use of electrical energy. Natural gas thermoelectric generation is an alternative to guarantee energy supply in times when water conditions are unfavorable in Brazil, with lower greenhouse gas emissions when compared to other thermal sources. The justification for this study is to demonstrate the importance of using natural gas thermoelectric plants and to demystify the image that this type of plant only brings environmental disadvantages with high production costs, considering the scarcity of research on the use of this type of plant in the country. Being analyzed through a case study, a natural gas thermoelectric plant located in Araucária - PR, the objectives of the study were achieved, evaluating the history of energy generation of the plant, which made its importance in periods of water scarcity in Brazil evident, being used within the National Interconnected System as a backup in times when hydroelectric generation was deficient, providing security and stability to the national generating park. The positive points include the reduction of CO₂ emissions and the complementarity with renewable energy sources, the construction time of which takes 2 to 3 years, together with operational flexibility. The negative points include the emission of methane (CH₄) and nitrogen oxides (NOₓ). There is still dependence on imports and volatile natural gas prices that can make the production process more expensive. In short, it was possible to verify that UTE Araucária plays a prominent role in guaranteeing the supply of electricity in Brazil, demonstrating how important a natural gas-fired thermal plant is for the country, demystifying the view that this type of plant is only harmful to the environment.